Synthesis of ZIF-8 based composite hollow fiber membrane with a dense skin layer for facilitated biogas upgrading in gas-liquid membrane contactor - Xu, Yilin (2020)
Gas-liquid membrane contactor (GLMC) has been regarded as a promising alternative to conventional contacting processes for CO2 absorption. In this work, a composite hollow fiber (HF) membrane with an aminosilane-modified zeolitic imidazolate framework-8 (mZIF-8) based dense skin layer was designed and synthesized for high-efficiency biogas upgrading in the GLMC process, by dispersing mZIF-8 nanocrystals into poly(dimethylsiloxane) matrix and then depositing on a porous polyvinylidene fluoride (PVDF) substrate. (3-aminopropyl)triethoxysilane was introduced to modify the ZIF-8 nanocrystals, thereby enabling the chemical bonding with PDMS chains for avoiding interfacial voids and further enhancing hydrophobicity. Compared with the control membrane, the newly developed mZIF-8 based composite membrane with a dense skin exhibited competitive hydrophobicity with a contact angle of 130°, ensuring its anti-wetting ability. It exhibited an enhanced biogas upgrading performance with the absorption fluxes of 2.3 and 3.8 × 10−3 mol m−2·s−1 using water and 1 M monoethanolamine (MEA) as absorbents, respectively (liquid velocity = 0.25 m s−1). In particular, a comparable selectivity of CO2/CH4 with the value of ∼20 was achieved by using MEA as absorbent in the GLMC process. A robust long-term stability of the mZIF-8 based composite HF membrane was also achieved in a 15-day operation. This work offers a new perspective for promoting CO2 mass transfer with mZIF-8 based composite HF membranes, thereby improving the biogas upgrading performance in GLMC applications.